2022
DOI: 10.3389/fimmu.2022.1090989
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and endoplasmic reticulum in podocytopathy during diabetic nephropathy progression

Abstract: Proteinuria or nephrotic syndrome are symptoms of podocytopathies, kidney diseases caused by direct or indirect podocyte damage. Human health worldwide is threatened by diabetic nephropathy (DN), the leading cause of end-stage renal disease (ESRD) in the world. DN development and progression are largely dependent on inflammation. The effects of podocyte damage on metabolic disease and inflammatory disorders have been documented. Epigenetic and endoplasmic reticulum (ER) stress are also evident in DN. Targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 128 publications
(156 reference statements)
0
5
0
Order By: Relevance
“…Endoplasmic reticulum (ER) stress occurs when proteostasis in the ER is broken with an accumulation of misfolded and unfolded proteins, which is strongly associated with podocyte injury in DKD. 91 LINC01619 and TCF7 have been shown to mediate ERS and cause podocyte injury. LINC01619 functions biologically as a sponge for miR-27a, and in HG-treated MPC-5, LINC01619 is underexpressed and miR-27a is overexpressed, which downregulates forkhead box O1 (FOXO1) to activate ERS and causes podocyte injury.…”
Section: Lncrnas and Endoplasmic Reticulume Stress In Podocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoplasmic reticulum (ER) stress occurs when proteostasis in the ER is broken with an accumulation of misfolded and unfolded proteins, which is strongly associated with podocyte injury in DKD. 91 LINC01619 and TCF7 have been shown to mediate ERS and cause podocyte injury. LINC01619 functions biologically as a sponge for miR-27a, and in HG-treated MPC-5, LINC01619 is underexpressed and miR-27a is overexpressed, which downregulates forkhead box O1 (FOXO1) to activate ERS and causes podocyte injury.…”
Section: Lncrnas and Endoplasmic Reticulume Stress In Podocytesmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress occurs when proteostasis in the ER is broken with an accumulation of misfolded and unfolded proteins, which is strongly associated with podocyte injury in DKD 91 . LINC01619 and TCF7 have been shown to mediate ERS and cause podocyte injury.…”
Section: Lncrnas Affect Various Pathologic Changes In Dkdmentioning
confidence: 99%
“…Epigenetic mechanisms such as histone modifications and microRNA regulation are believed to assist in physiological adjustments to environmental conditions. Components of epigenetic modulation, including noncoding RNAs (ncRNAs), histone deacetylases (HDACs), and DNA methylation, were all found to play a unique role in DKD progression [40,41]. Studies have shown that persistent inflammation and cytokine exposure under diabetic conditions leads to epigenetic modifications, and ultimately induces lasting open chromatin structures at pathological gene sites, a possible mechanism for "metabolic memory" [42].…”
Section: New Prospects In Gene and Epigenetic Regulationmentioning
confidence: 99%
“…CHOP, in the subsequent cascade, regulates the balance between pro- and anti-apoptotic Bcl-2 family members, leading to caspase activation [ 8 ]. ER stress has been implicated in pathophysiology of various renal diseases, including DN, with ER stress-induced apoptosis playing a crucial role [ [9] , [10] , [11] ]. Consequently, targeting ER stress inhibition has emerged as a promising therapeutic approach for DN treatment.…”
Section: Introductionmentioning
confidence: 99%